Sinergi dalam Mewujudkan Pendidikan Berkualitas di Wilayah 3T Kabupaten Malinau, Provinsi Kalimantan Utara: Kegiatan di SMAN 10 Bahau Hulu - R, Nurmala; Mansur, Achmad Zultan (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
This community service initiative aims to facilitate and support the accreditation process at SMAN 10 Bahau Hulu, a high school located in a 3T (frontier, outermost, disadvantaged) region in Malinau Regency, North Kalimantan. The activities involved direct visits to the partner school to identify factors hindering student achievement, describe infrastructure and accessibility conditions, and formulate strategies for improving education quality relevant to local needs. Data collection methods included field and classroom observations, interviews, questionnaires, and documentation studies. The visit results indicate that the school has strengths in creating an inclusive learning environment and effective governance, but it also faces challenges related to optimizing learning, developing teacher professionalism, and limited resources. These challenges, compounded by geographic isolation and socio-cultural barriers, necessitate targeted support to ensure the school meets national accreditation standards and delivers equitable, quality education. This community service activity contributes to an understanding of school evaluation practices in 3T regions and provides follow-up recommendations for improving educational quality.